2004
DOI: 10.1002/app.20481
|View full text |Cite
|
Sign up to set email alerts
|

1H‐NMR investigation of the thermooxidation degradation of poly(oxymethylene) copolymers

Abstract: ABSTRACT:The thermooxidative degradation of poly-(oxymethylene) copolymer (CPOM-Y) powder was studied in air in 150°C. The effect of the sequence distribution of degraded poly(oxymethylene) (POM) samples on the thermal decomposition behavior was investigated with 1 H-NMR and gas chromatography/mass spectrometry. The results showed that the degradation process of CPOM-Y could be divided into three stages with a gradually increasing degradation rate. The change in the sequence molar fractions agreed with the fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 16 publications
1
12
0
1
Order By: Relevance
“…The degradation rate of chain scission is higher than that of the initial step; in chains with higher molar mass, more formaldehyde formation occurs and the degradation rate increases linearly with increasing molar mass. On the other hand, Pan et al [6] postulated that the degradation process of POM copolymer could be divided into three stages with a gradually increasing degradation rate: (1) At the beginning, POM chain tends to split off formaldehyde, starting at the chain ends, some of which were not ended by ethylene oxide (EO) units; (2) in the second stage, the thermooxidation of POM takes place in the amorphous phase, and finally, in the last stage, further random chain scission and unzipping occur in the crystalline phase. In the work done by Archodoulaki et al [11], it was found that the onset temperature of degradation for POM copolymer with the highest average molar mass was the highest.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The degradation rate of chain scission is higher than that of the initial step; in chains with higher molar mass, more formaldehyde formation occurs and the degradation rate increases linearly with increasing molar mass. On the other hand, Pan et al [6] postulated that the degradation process of POM copolymer could be divided into three stages with a gradually increasing degradation rate: (1) At the beginning, POM chain tends to split off formaldehyde, starting at the chain ends, some of which were not ended by ethylene oxide (EO) units; (2) in the second stage, the thermooxidation of POM takes place in the amorphous phase, and finally, in the last stage, further random chain scission and unzipping occur in the crystalline phase. In the work done by Archodoulaki et al [11], it was found that the onset temperature of degradation for POM copolymer with the highest average molar mass was the highest.…”
Section: Introductionmentioning
confidence: 98%
“…However, these comonomer units strongly affect the thermal and chemical behavior of the copolymer. Thus, the properties of POM copolymers depend on the comonomer composition and on the sequence distribution (e.g., random or block) of the constituent comonomers [6].…”
Section: Introductionmentioning
confidence: 99%
“…Commercial c-POMs are typically produced through the cationic copolymerization of trioxane and 0.1-15 mol % of a cyclic ether, such as ethylene oxide (EO), dioxolane, or 1,3,5-trioxepane. Acetal copolymers consist of POM segments with oxyethylene units distributed in the chain, which affect the thermal and chemical behavior of the copolymer [13]. According to Kern [14], degradation reactions in POM-homopolymers are also occurring in POM copolymers but the copolymer units hinder the unzipping of the polymer chain and the depolymerisation is stopped at the C-C bond of the copolymer unit [15].…”
Section: Introductionmentioning
confidence: 99%
“…We attributet hese to water-soluble polyoxomethylenes (POM) which have am olecular formula of HO(CH 2 O) n H. The reported 1 HNMR spectrum of POM species from formaldehyde presentss ignals at around 1.9-2 ppm (OH) and % 4.5-5.2 ppm (CH 2 -O). [44][45][46] The peaks at around 4-5 ppm would have been obscured by the only partially suppressed water signal. In aqueous solution HCHO is known to polymerise to linear POM, where n can be as high as 100, [44][45][46] and in this respect zeolites are known to promote POM formation.…”
Section: Resultsmentioning
confidence: 99%
“…[44][45][46] The peaks at around 4-5 ppm would have been obscured by the only partially suppressed water signal. In aqueous solution HCHO is known to polymerise to linear POM, where n can be as high as 100, [44][45][46] and in this respect zeolites are known to promote POM formation. [47] Low molecular weightP OM (n < 8) is water-soluble.…”
Section: Resultsmentioning
confidence: 99%